In vitro Evaluation of the Combinatory Antibacterial and Antiproliferative Effects of Ciprofloxacin and Curcumin-Quercetin Mixture - Guran, M.; Altundag, E. M.; Sanliturk, G.; Usturk, S. (Pleiades Publishing Inc, 2025)
Antibacterial resistance, particularly involving methicillin-resistant Staphylococcus aureus (MRSA), poses a significant challenge to global healthcare. This study investigates the synergistic effects of a polyphenolic mixture of curcumin (C) and quercetin (Q), (QC) combined with ciprofloxacin (CIP) to evaluate their antibacterial and antiproliferative potential in vitro. Minimum inhibitory concentrations (MICs) of CIP, C, and Q against MRSA were determined using the broth microdilution method. Synergistic interactions between QC and CIP were assessed through the checkerboard assay, while the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay evaluated cell viability in human colorectal carcinoma HCT-116 cancer cells treated with the combinations. The degree of synergism was calculated using the Chou-Talalay method and expressed as a combination index. The MICs were 9.8 ng/mL for CIP, 15.500 ng/mL for C, and 7.750 ng/mL for Q. A strong synergistic effect was observed with a fractional inhibitory concentration index (Sigma FICI) of 0.3125, resulting in 16-fold reduction in the MIC of CIP when combined with QC (23.44 ng/mL QC and 0.61 ng/mL CIP). Additionally, the QC-CIP combination significantly enhanced antiproliferative effects, reducing the IC50 in HCT-116 cells by 12-fold compared to monotherapies. These findings suggest that the QC-CIP combination holds potential as an effective strategy to combat MRSA infections and inhibit cancer cell proliferation. Future in vivo studies are warranted to confirm its clinical applicability.
Keywords: curcumin; quercetin; ciprofloxacin; synergy; checkerboard; anti-cancer